Head Position and Intraocular Pressure in the Lateral Decubitus Position. Issue 1 (January 2015) - Seo, Hyejin; Yoo, Chungkwon; Lee, Tae-Eun; Lin, Shan; Kim, Yong Yeon
ABSTRACT Purpose To investigate the effects of different head positions in the lateral decubitus posture on intraocular pressure (IOP). Methods Seventeen healthy Korean subjects were included in this prospective observational study. Intraocular pressure measurements were taken with the subjects in the sitting position and the recumbent positions including supine, right lateral decubitus, and left lateral decubitus positions. In right and left lateral decubitus positions, IOP measurements were taken with three different head positions (30 degrees higher, 30 degrees lower, and parallel to the center of the thoracic vertebra) in a randomized sequence. Intraocular pressure was measured using the ICare Pro tonometer in both eyes 5 minutes after assuming each posture. The eye on the lower side in the lateral decubitus position was termed as the dependent eye. We assessed differences in the IOP of the dependent and nondependent eyes in the lateral decubitus positions with different head positions. Results Regardless of the head position, the dependent eyes showed higher IOP than the nondependent eyes in the lateral decubitus positions except in the left lateral decubitus with high head position (p < 0.001 for all positions except left lateral decubitus, p = 0.083). Low head position significantly increased the IOP of dependent eyes, compared with the neutral or high head positions in lateral decubitus posture. Conclusions Low head position elevates the IOP of the dependent eyes compared with neutral head position in the lateral decubitus posture. Proper adjustment of the height of a pillow may help mitigate IOP elevations resulting from lying on the side with a low pillow or with no pillow.